Aortic Atherosclerosis: A Common Source of Cerebral Emboli, Often Overlooked!. (January 2016) - Ismail, Imtiaz; Agarwal, Anushree; Aggarwal, Saurabh; Al-Khafaji, Nawfal; Gupta, Navdeep; Badi, Hani; Chopra, Aashish; Khosla, Sandeep; Arora, Rohit
Abstract : Aortic atherosclerotic plaques are usually seen in males older than 55 years who are known to have risk factors of atherosclerosis. Recent large series of consecutive stroke patients reported that the prevalence of aortic atheromatous plaques in patients with stroke is about 21%–27%, which is in the same magnitude when compared with the prevalence of carotid disease (10%–13%) and atrial fibrillation (18%–30%). Atheromatous plaques are composed of a lipid pool, a fibrous cap, smooth muscle cells, and mononuclear cell infiltration with calcification. Aortic plaques can cause embolization to brain, extremities, or visceral organs. Atheroembolization can occur spontaneously or as a result of manipulation during cardiac or vascular surgery. Only few cases of cerebral embolization from an aortic plaque in the absence of any manipulation have been described. Although few atherosclerotic plaques can be visualized on the aortogram, transesophageal echocardiogram remains a preferred modality for diagnosis in such cases. We present a case of cerebral embolism arising from a mobile noncalcified complex aortic arch plaque diagnosed on a transesophageal echocardiogram and review the literature on its diagnosis, clinical implications, and management.